(untitled) (Vietnam Journal of Community Medicine, 2024)
Ojective: This study aims to evaluate the effect on pulmonary function tests after abdominal surgery in the elderly treated postoperatively with CPAP in JPAP device versus traditional oxygen delivery systems. Patients and method: 60 patients aged 60 years or older undergoing abdominal surgery were divided into 2 groups. Both groups were given oxygen at 5 liters/minute. In addition, the experimental group received CPAP through the nasal mask after surgery for 4 hours. Results: 60 patients (36 male, 24 female) were divided into 2 groups, each group of 30 patients. There were no significant differences between the 2 groups in terms of age, gender, BMI, ASA, type of surgery and surgery time. In the experimental group, there was an improvement in respiratory rate, SpO2 and PaO2 compared to the control group. Specifically, breathing rate, SpO2, PaO2 in the intervention group were 15.9 ± 1.3; 96.0 ± 0.9; 79.8 ± 5.0 respectively; compared to 15.1 ± 1.6; 95.0 ± 1.2; 77.2 ± 5.9 in the control group (p < 0.05). There was no difference in FEV1, FVC, FEV1/FVC, PEF between the 2 groups (p > 0.05). Conclusion: The JPAP device with CPAP breathing mode is a convenient, safe device that effectively improves some pulmonary function tests after abdominal surgery in the elderly.